1985
DOI: 10.2118/12003-pa
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Processes In In-Situ Combustion of Light Oil Reservoirs

Abstract: To interpret and optimize field performance of in-situ combustion, dominant chemical and physical mechanisms comprising the displacement process must be understood, and the influence of reservoir characteristics and operating procedures in determining swept areas of the reservoir must be established. This paper addresses important aspects of these factors via a numerical simulation study. Vaporization of the oil, changes in oil volatility due to coking, and changes in oil properties due to low temperature oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Thus, it can be considered that some of these surfactants can be potentially generated along the oxidation of crude oils at low temperature. 12 Although asphaltenes have been acknowledged as natural surfactants and considered as the main emulsion stabilizers, 10,11,13−16 it is more precise to describe the stabilization in water−crude oil emulsions, in terms of ionizable species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be considered that some of these surfactants can be potentially generated along the oxidation of crude oils at low temperature. 12 Although asphaltenes have been acknowledged as natural surfactants and considered as the main emulsion stabilizers, 10,11,13−16 it is more precise to describe the stabilization in water−crude oil emulsions, in terms of ionizable species.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that water-in-oil (W/O) emulsions stability can be explained by the presence of inorganic solids such as clay, sandstone, and corrosion products, or the action of petroleum’s natural surfactants. These compounds interact amid the W/O interface, because they bear functional groups allowing them to interact both with oil and water phases. Thus, it can be considered that some of these surfactants can be potentially generated along the oxidation of crude oils at low temperature …”
Section: Introductionmentioning
confidence: 99%
“…They showed that the physical, chemical and fluid flow characteristics dramatically affected the ISC process [9]. Another numerical model was presented by Smith and Perkins [10], who had studied and simulated the heat transfer, vaporization, condensation and fluid flow pattern during wet ISC at reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Upscaled reaction kinetics result in lower combustion temperatures and consequently less oil vaporization and more residual oil left for combustion 19 . The net result is that the model underestimates the predicted combustion front velocity.…”
mentioning
confidence: 99%
“…19 Kumar 22 Sakthikumar et al 8 Fraim et al 10 Glandt et al 7 Ren et al 25 Kuhlman 20 Pascual et al 12 Year 26 Kumar 22 In paper NA NA In paper None In paper…”
mentioning
confidence: 99%